Gambaran Pengetahuan Masyarakat Kecamatan Selat Dalam Tentang Swamedika Demam Menggunakan Parasetamol - Fitriya Fitriya; Muhammad Zaini; Muliyani Muliyani (JEMPOL : Jurnal Elektronik Mahasiswa Polanka, 2024)
Self-medication is the use of drugs without prior medical consultation regarding the indications, dosage, and duration of treatment carried out. Fever is the body's natural process of fighting infections that enter the body when the temperature rises beyond normal body temperature (>37.5°C). Paracetamol is a drug used to reduce or eliminate pain and lower high body temperature. This study aims to determine the level of public knowledge in fever self-medicating using paracetamol in Selat Dalam District, Kapuas Regency. This research was quantitative with a descriptive survey design using a questionnaire. The sample of this study was the community of Selat Dalam District, Kapuas Regency, taken by observational method, namely 72 respondents with the highest percentage the highest were women with 41 people (57%), the age group of 17-25 years with 23 people (32%), employment as private employees with 20 people (27%), and high school education with 36 people (50%). The percentage of the level of public knowledge about fever self-medicating using paracetamol is 80% with a good category.